Pengaruh Penggunaan Smartphone terhadap Nilai Akademik Mahasiswa - Naova Maria (Bina Nusantara University, 2013)
Advances in technology are now starting to lead to mobile-based technologies. Thus, the use of smartphones is increasingly favored by public, especially college students that are discussed in this study. Effects of smartphones use is discussed emergingly in which many studies state that smartphone brings negative side effects as well as positive side effects. Therefore, this study will discuss the side effects of smartphone use among college students towards academic values obtained in the course (GPA) in order to determine whether smartphone use brings influence on students' academic value or not.